Identification of a novel long-acting 4’-modified nucleoside reverse transcriptase inhibitor against HBV - Higashi-Kuwata, Nobuyo; Hayashi, Sanae; Kumamoto, Hiroki; Ogata-Aoki, Hiromi; Das, Debananda; Venzon, David; Hattori, Shin-ichiro; Bulut, Haydar; Hashimoto, Mai; Otagiri, Masaki; Takamune, Nobutoki; Kishimoto, Naoki; et al. (Journal of hepatology, 2021)
While certain nucleos(t)ide reverse transcriptase inhibitors (NRTIs) are efficacious in treating HBV infection, their effects are yet to be optimized and the emergence of NRTI-resistant HBV variants is an issue because of the requirement for lifelong treatment. The development of agents that more profoundly suppress wild-type and drug-resistant HBVs, and that have a long-acting effect, are crucial to improve patient outcomes. Herein, we synthesized a novel long-acting 4’-modified NRTI termed E-CFCP. We tested its anti-HBV activity in vitro, before evaluating its anti-HBV activity in HBV-infected human-liver-chimeric mice (PXB-mice). E-CFCP’s long-acting features and E-CFCP-triphosphate’s interactions with the HBV reverse transcriptase (HBV-RT) were examined. E-CFCP potently blocked HBVWTD1 production (IC50qPCR_cell=1.8 nM) in HepG2.2.15 cells and HBVWTC2 (IC50SB_cell=0.7 nM), entecavir (ETV)-resistant HBVETV-RL180M/S202G/M204V (IC50SB_cell=77.5 nM), and adefovir-resistant HBVADV-RA181T/N236T production (IC50SB_cell=14.1 nM) in Huh7 cells. E-CFCP profoundly inhibited intracellular HBV DNA production to below the detection limit, but ETV and tenofovir alafenamide (TAF) failed to do so. E-CFCP also showed less toxicity than ETV and TAF. E-CFCP better penetrated hepatocytes and was better tri-phosphorylated; E-CFCP-triphosphate persisted intracellularly for longer than ETV-triphosphate. Once-daily peroral E-CFCP administration over 2 weeks (0.02~0.2 mg/kg/day) reduced HBVWTC2-viremia by 2–3 logs in PXB-mice without significant toxicities and the reduction persisted over 1–3 weeks following treatment cessation, suggesting once-weekly dosing capabilities. E-CFCP also reduced HBVETV-RL180M/S202G/M204V-viremia by 2 logs over 2 weeks, while ETV completely failed to reduce HBVETV-RL180M/S202G/M204V-viremia. E-CFCP’s 4’-cyano and fluorine interact with both HBVWT-RT and HBVETV-RL180M/S202G-M204 -RT via Van der Waals and polar forces, being important for E-CFCP-triphosphate’s interactions and anti-HBV potency. E-CFCP represents the first reported potential long-acting NRTI with potent activity against wild-type and treatment-resistant HBV. Although there are currently effective treatment options for HBV, treatment-resistant variants and the need for lifelong therapy pose a significant challenge. Therefore, the development of new treatment options is crucial to improve outcomes and quality of life. Herein, we report preclinical evidence showing that the anti-HBV agent, E-CFCP, has potent activity against wild-type and treatment-resistant variants. In addition, once-weekly oral dosing may be possible, which is preferrable to the current daily dosing regimens. [Display omitted] •E-CFCP potently reduces HBV viremia without significant toxicity in human liver chimeric mice.•E-CFCP efficiently penetrates into and is tri-phosphorylated in human hepatocytes.•E-CFCP represents the first reported long-acting NRTI with potent anti-HBV activity.